Cognitive load and working memory: a system view of measurement. (2nd January 2021) - Shearer, Rick L.; Yu, Junxiu; Peng, Xinyun
ABSTRACT: Within the fields of learning design, instructional systems and educational psychology, cognitive load has been discussed and debated for a number of years. The impact of course designs on learning process is still questioned, and how we learn continues to be an intriguing question. The fields of working memory (WM) and cognitive load (CL) have strived to explore this question over the years. This paper proposes a systems model to explore the overlaps of these concepts. Different types of load feedback within the systems model are discussed. The proposed model is simplified by introducing the idea of active and distracted WM. The model is conceptualised through the lens of learners interacting with page designs while studying through an online distance programme. We present the concepts as a stock and flow diagram, with related equations. The model allows us to bridge WM and CL and forms the foundation for testing the three types of cognitive load and how they interact in our course designs.